2003
DOI: 10.1046/j.1365-2672.2003.01971.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to high salt in Lactobacillus: role of peptides and proteolytic enzymes

Abstract: Aims: To study the influence of peptides and proteolytic enzymes in the osmotic adaptation of Lactobacillus casei. Methods and Results: Di-and tri-peptides added individually increased the osmotolerance of Lact. casei when grown in a chemically defined medium (CDM) containing NaCl. Growth stimulation and the reestablishment in their presence of plasmid DNA supercoiling (recovery of the linking number) in hyperosmotic medium indicated that they are used as osmocompatible solutes as carnithine a known osmoprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 26 publications
5
48
0
Order By: Relevance
“…Although most species of LAB are unable to grow at such high NaCl concentrations, the halophilic lactic acid bacterium Tetragenococcus halophilus can grow in such a severe environment and plays an important role in deepening the taste and aroma of miso. It has been reported that unconventional microorganisms adapted to such severe environments have special structures and compositions which differ from those of LAB growing in a low or no NaCl environment (Piuri et al, 2003;Piuri et al, 2005) such as fermented milk, yogurt. Therefore, it is postulated that LAB growing in a high concentration of NaCl have different beneficial functions from LAB in yogurt, and may have stronger activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although most species of LAB are unable to grow at such high NaCl concentrations, the halophilic lactic acid bacterium Tetragenococcus halophilus can grow in such a severe environment and plays an important role in deepening the taste and aroma of miso. It has been reported that unconventional microorganisms adapted to such severe environments have special structures and compositions which differ from those of LAB growing in a low or no NaCl environment (Piuri et al, 2003;Piuri et al, 2005) such as fermented milk, yogurt. Therefore, it is postulated that LAB growing in a high concentration of NaCl have different beneficial functions from LAB in yogurt, and may have stronger activities.…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying for several years the biochemical and biophysical characteristics of the cell envelopes of cells grown under osmotic stress both in B. subtilis and in Lactobacillus casei (Ló pez et al, , 2001(Ló pez et al, , 2002Piuri et al, 2003;Machado et al, 2004;Piuri et al, 2005). In these studies, the analysis of membrane lipids has revealed that there is a significant increase in the anionic lipid fraction such as phosphatidylglycerol (PG) and especially cardiolipin (CL) when B. subtilis cells are grown in LB medium containing 1?5 M NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…Assay of peptidase activity X-Prolyl dipeptidyl aminopeptidase activity (PepXP) of CFE was measured according to Piuri et al (2003). Gly-Pro-pNA was used as a substrate.…”
Section: Methodsmentioning
confidence: 99%